2023
DOI: 10.7759/cureus.36323
|View full text |Cite
|
Sign up to set email alerts
|

New Onset Multiple Sclerosis Post-COVID-19 Vaccination and Correlation With Possible Predictors in a Case-Control Study

Abstract: Introduction: Various inflammatory diseases have been associated with the administration of various vaccines. Several reports have associated vaccine administration with the demyelinating diseases of the central nervous system (CNS). However, no clear or strong scientific evidence exists to support the association of vaccine administration with the onset of demyelinating diseases. Some CNS demyelination diseases such as acute disseminated encephalomyelitis (ADEM) and neuromyelitis optica spectrum disorders (NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Toljan and coll. described a series of ve patients who developed MS during 1 daytwo months' timeframe after a mRNA-based COVID-19 vaccine [22]. In Oxford COVID Vaccine Trial, one case of MS reactivation 10 days after rst dose of ChAdOx1 vaccine was observed among 11636 participants [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Toljan and coll. described a series of ve patients who developed MS during 1 daytwo months' timeframe after a mRNA-based COVID-19 vaccine [22]. In Oxford COVID Vaccine Trial, one case of MS reactivation 10 days after rst dose of ChAdOx1 vaccine was observed among 11636 participants [23].…”
Section: Discussionmentioning
confidence: 99%
“…The time interval by which to de ne a temporal relationship between a triggering event (e.g., a vaccine) and the onset of MS is controversial. We established a one-month timeframe based on recent literature about in ammatory events related to SARS-CoV-2 vaccination [17]; the same timeframe was chosen by Alluqmani in his casecontrol study including thirty-two patients with vaccine-related MS onset [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the early stages of vaccination campaigns, in late 2020, many cases of neurological disorder onset after vaccination were reported [24][25][26][27]. A few cases of reactivation or new onset of demyelinating diseases of the CNS have been described as well, both after vaccination with mRNA-based [28][29][30][31] and with adenovirus-vectored formulations of the vaccine [31][32][33]. The assumption that anti-COVID-19 vaccination may increase the risk of developing MS is still debated, and this potential causal relationship could change the risk-benefit profile of anti-COVID-19 vaccination, at least in some population subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Our study clearly suggests that COVID-19 mRNA vaccines had the highest number of vaccine-associated MS reports, which was significantly disproportionate to vaccineassociated MS reporting. COVID-19 vaccines were granted with emergency use authorization, and several case reports of vaccineassociated MS pointed out safety concerns 6,[33][34][35][36][37][38]. Moreover, Ad5vectored COVID-19 vaccines and inactivated whole-virus COVID-19 vaccines did not exhibit disproportionate MS signals among the various vaccines analyzed 39.…”
mentioning
confidence: 99%